2019
DOI: 10.5603/kp.a2019.0034
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the CHA2DS2-VASc score and atrial fibrillation in patients hospitalised due to heart failure

Abstract: Background: Heart failure (HF) has become an epidemic. A similar situation is also observed for atrial fibrillation (AF). The CHA 2 DS 2 -VASc score is one of the most useful tools for thromboembolic risk assessment. Aim:The aim of the study was to assess the prevalence of AF in patients with decompensated HF, who were divided into subgroups according to the CHA 2 DS 2 -VASc score. Methods:We analysed the prevalence of AF in a group of 1108 patients (327 women) hospitalised due to HF decompensation in medical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 18 publications
(21 reference statements)
0
3
0
Order By: Relevance
“…e variables that comprise the CHA2DS2-VASc score have been extensively studied as risk factors for death and adverse events in patients with acute STEMI [17][18][19]. In addition, numerous studies have shown that that CHA2DS2-VASc score can predict the prognosis of patients with various cardiovascular diseases, regardless of atrial fibrillation [20][21][22][23]. In patients diagnosed with the acute coronary syndrome, the CHA2DS2-VASc score was also associated with adverse cardiovascular events.…”
Section: Discussionmentioning
confidence: 99%
“…e variables that comprise the CHA2DS2-VASc score have been extensively studied as risk factors for death and adverse events in patients with acute STEMI [17][18][19]. In addition, numerous studies have shown that that CHA2DS2-VASc score can predict the prognosis of patients with various cardiovascular diseases, regardless of atrial fibrillation [20][21][22][23]. In patients diagnosed with the acute coronary syndrome, the CHA2DS2-VASc score was also associated with adverse cardiovascular events.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of AF in patients with HFpEF might vary among the populations from different regions or ages 3 . Previously, Kuczaj et al 22 . found that the CHA2DS2‐VASc score could be used to detect patients with decompensated HF characterized by the highest prevalence of AF.…”
Section: Discussionmentioning
confidence: 99%
“…21 The prevalence of AF in patients with HFpEF might vary among the populations from different regions or ages. 3 Previously, Kuczaj et al 22 found that the CHA2DS2-VASc score could be used to detect patients with decompensated HF characterized by the highest prevalence of AF. In our study, the AF prevalence rates in HFpEF patients with a score of ≥3 increased in a graded manner across the CHADS2 (range: 39.1-56.7%), R2CHADS2 (range: 35.9-71.4%), or CHA2DS2-VASc (range: 28.0-50.0%) score categories.…”
Section: Comparisons With Previous Studiesmentioning
confidence: 99%